HISTORIA IN WESTERN SCHOLARSHIP TRADITION: WHERE NATURAL SCIENCES AND HUMANITIES COLLIDED - Gani Ahmad Jaelani (Jurnal Kajian Wilayah, 2020)
This article aims to analyse the concept of historia as the root of the discipline of history today. Historia is a concept in scientific tradition which dates back to Greek era. Today, the concept is only linked to the historical discipline still using the same name. Nevertheless, the concept was used to cover several studies such as natural studies, medicine, and humanities. This article will trace the evolution of the concept in the European scientific tradition since it was introduced for the first time. Furthermore, this article will discuss as well the problem of historia which raises the debate about the status of Herodotus as the Father of History. Finally, this article will elaborate to which extent the concept of historia becomes a junction between several professions, especially historian and physician. It is important to carry out this study to analyse the development of knowledge in Europe as the foundation that later develops in other places.